Lay Explanatory Models of Depression and Preferred Coping Strategies among Somali Refugees in Norway. A Mixed-Method Study - Markova, Valeria; Sandal, Gro M. (Frontiers in Psychology, 2016)
Objective. Refugees are at high risk for mental health problems due to trauma in their pasts and to acculturation stress as they settle in a new country. To develop efficient health services to meet the needs of refugees from various regions, an understanding of how they make sense of and prefer to cope with mental health problems is warranted. This study aims to investigate lay explanatory models of depression and preferred coping strategies among Somali refugees in Norway. Methods. The study used a mixed-method design with a vignette describing a moderately depressed person based on ICD-10 criteria. Firstly, a survey study was performed among Somali refugees (n = 101). Respondents were asked to provide advice to the vignette character, completing the Cross-Cultural Depression Coping Inventory and the General Help-Seeking Questionnaire. Secondly, focus group interviews (n = 10) were done separately with males and females to examine the relationship between the explanatory models of depression and preferred coping strategies. Results. The participants showed a strong preference for coping with depression by religious practices and reliance on family, friends, and their ethnic/religious community rather than seeking professional treatment from public health services (e.g., medical doctors, psychologists). Depressive symptoms were conceptualized as a problem related to cognition (thinking too much) and emotion (sadness), but not with biological mechanisms, and were thought to result from spiritual possessions, stress from social isolation, and/or past trauma. Independent of time in exile, the participants showed a strong identification with their ethnic origin and associated values. As participants emphasized the need to obey and follow the viewpoint of elders, fathers, and spiritual leaders, these authorities seemed to be “gatekeepers” for access to mental health services. Conclusion. The results highlight that mental health programs for Somali refugees should actively involve the ethnic community, including spiritual leaders, to reach patients in need and to foster treatment compliance.